2007
DOI: 10.1080/07357900701600954
|View full text |Cite
|
Sign up to set email alerts
|

Downregulation of Survivin Is Associated With Reductions in TNF Receptors' mRNA and Protein and Alterations in Nuclear Factor Kappa B Signaling in Urothelial Cancer Cells

Abstract: Because survivin is selectively expressed in and associated with an unfavorable prognosis in transitional cell carcinoma of the bladder (TCC), we treated T-24 cells with survivin siRNA. Survivin siRNA treatment caused a profound decrease of survivin protein that was associated with decreased cell growth, a specific G2/M arrest and increased cytochrome c release. Microarray analysis of apoptosis genes showed that levels of 14/114 gene products were decreased after 72 hours treatment with survivin siRNA, includi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
8
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 23 publications
1
8
1
Order By: Relevance
“…Survivin knockdown induces polyploidy because survivin is, besides its function as inhibitor of apoptosis, an integral part of the chromosomal passenger complex, thereby regulating chromosome segregation and cytokinesis (32). In agreement with the results of this study, Ning et al and Takizawa et al showed apoptosis induction and an arrest in G2/M cell cycle phase after treatment of BCa cells with siRNAs targeted at survivin (29,33). …”
Section: Discussionsupporting
confidence: 93%
“…Survivin knockdown induces polyploidy because survivin is, besides its function as inhibitor of apoptosis, an integral part of the chromosomal passenger complex, thereby regulating chromosome segregation and cytokinesis (32). In agreement with the results of this study, Ning et al and Takizawa et al showed apoptosis induction and an arrest in G2/M cell cycle phase after treatment of BCa cells with siRNAs targeted at survivin (29,33). …”
Section: Discussionsupporting
confidence: 93%
“…35 ± 5.24% for Panc-1 and BxPC3, respectively (P \ 0.05), compared with the control groups, while there was no difference between the blank control and negative control groups survivin may play an important role in the development of pancreatic cancer. Takizawa et al [32] showed that the downregulation of survivin causes changes in mitosis and apoptosis, which may be related to changes in TNF receptors and NF-jB signaling.…”
Section: Discussionmentioning
confidence: 98%
“…Moreover, it is known to be overexpressed and related with more aggressive behavior, increased tumor recurrence, chemotherapy resistance, increased survival in various tumors [3][4][5][6][10][11][12][13][14][15]. In TC, Haghpanah et al reported the significantly higher survivin expression in TC than in follicular adenoma, and Ito et al reported the significant link between survivin expression and the dedifferentiation of TC [16,17].…”
Section: Discussionmentioning
confidence: 99%